ACCULTURATION IN GOD'S BIRTHDAY CEREMONY KELENTENG SHIA DJIN KONG, JONGGOL - Desprosianasari, Ludovika; Hartati, C. Dewi (Bambuti, 2020)
This paper discussed the acculturation of Chinese and Sundanese culture in a ceremony at the Shia Djin Kong temple, Jonggol. On the right side of the temple there is a special room for the cult of Jonggol's ancestors, namely Embah Jago, Embah Sabin, Embah Surkat, Embah Jagakarsa, and Embah Nagawulung. In that room there are also many heirloom objects, such as keris, spears, lafadz Allah, and swords. Acculturation between Sundanese culture and Chinese culture can be seen at the birthday ceremony of the god Shia Djin Kong, which is the similarity between local culture and Chinese culture, in ancestor worship. The research method used in this writing is a qualitative research method, data collection techniques in this writing are participant observation, observation, and interviews to the temple officer, and people who come to pray both during the god's birthday ceremony and on ordinary days.